P162 Lynch syndrome followed up in a hereditary gynaecological cancer unit. (1st November 2019) - Veiga-Fernández, A; Móran, M; Oyonarte, MÁ; López Picado, A; Marquez-Rodas, I; Luque, MS; Mendizábal-Vicente, EM; Lizarraga-Bonelli, S
Abstract : Introduction/Background: Women with Lynch syndrome (hereditary nonpolyposis colorectal cancer) have a 40 to 60 percent lifetime risk of endometrial cancer and a 10 to 12 percent lifetime risk of ovarian cancer. Methodology: Retrospective observational study. Review of patients followed in the inherited cancer unit of the Gregorio Marañón university hospital between 1st January 2012 and 28th February 2019. The statistical analysis was carried out using SPSS 21.0. Results: During the indicated period, we followed 268 patients with confirmed genetic mutations that predispose to developing gynaecological cancer. Of the 268 patients, 10.8% (29/268) were carriers of genes related to Lynch syndrome. The most frequent mutation was MLH1 (15/29), followed by MSH2 (7/29) and MSH6 (4/29). 24/29 had a first-degree relative affected. Colorectal cancer was the most frequent (20/29). Within the cohort of patients carrying Lynch syndrome mutations, 12/29 were diagnosed with a first cancer (colorectal cancer in 5/29 and endometrial cancer in 2/29). The mean age at diagnosis of the primary tumor was 47±13 years. In this subgroup, 4/12 were diagnosed with a second cancer with a mean age at diagnosis of 61±15 years. Characteristics of these patients are summarized in table 1. The 2 patients with endometrial cancer were diagnosed in early stages and, after oncological surgery, didn't need adjuvant treatments. In 7/29 patients, primary prophylactic surgery was performed (total hysterectomy with bilateral salpingo-oophorectomy), with a mean age of 52±15 years. The histological analysis of prophylactic surgeries did not report malignancy. Conclusion: Patients carrying Lynch syndrome mutations should be followed in specialized hereditary cancer units, in tertiary hospitals. Prophylactic hysterectomy with bilateral salpingo-oophorectomy is recommended by current guidelines to prevent endometrial and ovarian cancer in these women. Disclosure: Nothing to disclose.